Allometric scaling to predict time trial performance and maximal oxygen consumption. Differences between male and female cyclist - Davidowitz, K. J.; Lambert, M. I.; Noakes, T. D.; Lamberts, R. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: A recent publication by Lambert et al (2012) showed allometric scaling of peak power output (PPO) was the most accurate method to predict 40km time trial (40km TT). This finding confirmed that the proposed allometric scaling method by Swain (1994) can, in addition to professional cyclists (Mujika et al, 1998), also be used in trained in well-trained male cyclist. However, as females have different body compositions than males, relatively higher body fat and lower muscle mass percentages, it is questionable if the same allometric scaling methods can also be used in female cyclists. Therefore the aim of this study was to determine if the same allometric scaling method used in male cyclists can also be used in female cyclists to predict 40km TT performance. Methods: Twenty trained to well-trained female cyclists (287 ± 25 W; 50.5 ± 3.4 ml/min/kg) , between the ages of 18 and 45 years, completed a peak power output (PPO) test (including respiratory gas analysis (VO2max)) and a 40km flat time trial (TT). All tests were performed between days 7 to 21 of the participant`s menstrual cycle to ensure that this had no effect on the measured performance parameters. After the tests, relationships between VO2max and 40km TT performance and absolute (W), relative (W/kg) and peak power output normalized for body mass to the exponent of 0.32 (W/kg 0.32) were determined. Relationships found in the female cyclists were compared to a data set of 45 trained to well-trained male cyclists (Lamberts et al. 2012). Results In the female cyclists, strong relationships were found between PPO and VO2max. A similar relationship between male and female cyclists was found when PPO and VO2max were expressed absolutely (W and l/min, respectively). However when PPO and VO2max were expressed relatively (W/kg and ml/min/kg, respectively) a similar slope but different y-axis intercept was found (p < 0.0001). In the female cyclists, 40km TT performance (s) also showed to have the strongest relationship with allometrically scaled PPO (r = - 0.87, 95% CI - 0.95 to - 0.70, p<0.0001). When this relationship was compared to male cyclists, a different slope was found alomtrically scaled PPO (W/kg 0.32) and 40km TT performance (s) (p = 0.0005681) Discussion: As in males, the strongest relationship with 40km TT time in female cyclists was found with allomatrically scaled PPO (W/kg 0.32). However when comparing the relationship found in female cyclists to male cyclists significant slope differences were found, suggesting that additional weight in female cyclists is less of an advantage when performing a flat TT performance than in male cyclists. This can possibly be explained by difference in body composition between male and females, as additional weight in females consists of relatively more body fat and less muscle mass than in males.